Approximate Next-to-Next-to-Leading Order Corrections to Hadronic Jet Production - de Florian, Daniel Enrique (2014)
We determine dominant next-to-next-to-leading order QCD corrections to single-inclusive jet produc- tion at the LHC and Tevatron, using the established threshold resummation framework. In contrast to previous literature on this topic, our study incorporates all of the following features: (1) It properly accounts for the way a jet is defined in experiment and treated in available full next-to-leading order calculations, (2) it includes the three leading classes of logarithmic terms in the perturbative expansion, and (3) it is adapted to the full kinematics in jet transverse momentum and rapidity relevant for experiments. A recent full next-to-next-to-leading order calculation in the purely gluonic channel allows us to assess the region where our approximate corrections provide an accurate description. We expect our results to be important on the way to precision jet phenomenology at the LHC and as a benchmark for further full next-to-next-to- leading order calculations.